2018
DOI: 10.1016/j.neuropsychologia.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in lower-alpha power during Ganzfeld flicker stimulation is associated with the production of imagery and trait positive schizotypy

Abstract: Light-flicker Ganzfeld (LFG) induces a lower to upper-alpha frequency shift. However, it is unclear how this neurophysiological response might relate to LFG-induced pseudohallucinatory phenomena. It is also unknown whether emotional states (e.g., fear) or traits associated with risk for psychosis (e.g., proneness to perceptual anomalies, ability to produce vivid mental imagery) affect such neurophysiological and/or perceptual responses to LFG.The present study investigated alpha sub-bands during LFG across sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Incidentally, several studies have found that visual flicker can elicit visual illusions, which have been reported across nearly the entire range of perceivable frequencies from delta to gamma (1 to ~ 50 Hz; Allefeld et al, 2011 ; Becker & Elliott, 2006 ). The strongest illusory experiences, however, are reported to occur in the range of 13.1–16 Hz (Sumich et al, 2018 ). These illusions occurred infrequently over continuous stimulation periods of at least 30 s. Another study found that it took, on average, over 8 s for illusory forms to emerge for various flicker frequencies (Becker & Elliott, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, several studies have found that visual flicker can elicit visual illusions, which have been reported across nearly the entire range of perceivable frequencies from delta to gamma (1 to ~ 50 Hz; Allefeld et al, 2011 ; Becker & Elliott, 2006 ). The strongest illusory experiences, however, are reported to occur in the range of 13.1–16 Hz (Sumich et al, 2018 ). These illusions occurred infrequently over continuous stimulation periods of at least 30 s. Another study found that it took, on average, over 8 s for illusory forms to emerge for various flicker frequencies (Becker & Elliott, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…"Ganzflicker" is a full-field, rhythmic visual flicker -a technique that is known to elicit pseudo-hallucinations and altered states of consciousness (Allefeld et al, 2011;Bartossek et al, 2021;Schwartzman et al, 2019;Sumich et al, 2018). In a recently published study (Königsmark et al, 2021), we found individual differences in reported susceptibility to visual pseudo-hallucinations after viewing 10 minutes of continuous red-and-black Ganzflicker at 7.5 Hz.…”
mentioning
confidence: 83%
“…The Ganzflicker experience is a full-screen visual flicker at 7.5 Hertz (Hz) frequency, alternating at 15 Hz between full-red and full-black, and embedded in an infinite while loop. Red flicker at various frequencies has previously been used to investigate both simple and complex anomalous experiences (Sumich et al, 2018), and was earlier found to produce larger differences in photic driving effects between visualizers and non-visualizers compared to green or blue flicker (Brown, 1966). We therefore used red flicker so that we could investigate anomalous percepts in the current study, and potentially use the same Ganzflicker protocol in a future study to investigate photic driving effects on the brain.…”
Section: Stimulimentioning
confidence: 99%
“…PH can be induced after several hours of sensory deprivation (e.g., blindfolding; Merabet et al, 2004), or several minutes of perceptual deprivation (e.g., filling the visual field with unstructured, uniform luminance called "Ganzfeld"; Schmidt & Prein, 2019;Zdravkovic, 2019). An under-explored method of inducing often intense and immediate PH (within seconds) is the use of rhythmic visual flicker (Allefeld et al, 2011;Gulbinaite et al, 2017;Sumich et al, 2018). Its easy implementation and immediate, robust effects make it a promising technique to investigate anomalous perception in an experimental setting.…”
mentioning
confidence: 99%